Foreign Language Anxiety in Academic Writing - Ariyanti, Ariyanti (Dinamika Ilmu: Jurnal Pendidikan, 2017)
Accomplishing an assignment in academic writing course is not as easy as pie because there are many aspects that students need to follow to have an English writing with a good quality. Particularly, this study is aimed to investigate Foreign Language Anxiety (FLA) in academic writing specifically to EFL students at university level. The factors that cause the students feel anxious in English writing represent on close-ended questionnaires that the researcher asks the students to answer. In addition, the researcher does direct observation by acting as a passive observer where she has no role in conducting or helping the lecturer in teaching the writing course. In this case, what the researcher does is finding an appropriate spot in classroom in order to have a clear description regarding with ongoing process of teaching and learning of writing course of English Department students at Widya Gama Mahakam University, Samarinda, Indonesia. As a result, data analyzed by using Likert Scale indicate that High Anxiety (HA) appears to be the highest level in students’ anxiety with nine out of sixteen anxiety statements. In addition, Moderate Anxiety (MA) is also showed on the result with six out of sixteen anxiety statements. Furthermore, although Low Anxiety (LA) appears in only one out of sixteen statements, it is correlated to other facts i.e. the apprehension of working with English writing assignment under time constraint, lack of self-confidence because of inadequate capability in English language proficiency such as structural rules in English as well as an ability to relate and compare theories among experts to support their writing. Further implication for better research and lecture of English writing course in the future is also pointed out in this study.